Malignancies Diagnosed During Pregnancy and Treated With Chemotherapy or Other Modalities (Review of 27 Cases): Multicenter Experiences. Issue 5 (1st June 2010) - Ustaalioglu, Bala Basak Oven; Gumus, Mahmut; Unal, Ali; Cayir, Kerim; Sever, Ozlem; Bilici, Ahmet; Elkran, Emin Tamer; Karaca, Halit; Benekli, Mustafa; Karaoglu, Aziz; Şeker, Mesut
Abstract : Background: Cancer is the second leading cause of death in women of reproductive age. The most common tumors diagnosed during pregnancy are breast and cervix cancer, Hodgkin lymphoma and non-Hodgkin lymphoma, leukemias, and malignant melanoma. The aim of therapy in pregnancy is to give optimal treatment to the mother without harm to the fetus. In the first trimester, organogenesis continues, so chemotherapy should not be given because of increasing risk of spontaneous abortion, fetal malformation, and mortality. We evaluated mostly seen tumors during pregnancy and assessed treatment type and outcome of pregnancy after chemotherapy in our population. Methods: We retrospectively analyzed 27 patients who have been treated during pregnancy or after the delivery because of several malignancies. Results: The tumors associated with pregnancy were breast cancer, hematologic malignancies, gynecologic malignancies, sarcomas, and others. The chemotherapy regimens were given in 17 of 27 patients in the second or third trimester of pregnancy. Four of the patients were diagnosed with cervical cancer, hemangiopericytoma, chronic myeloid leukemia, and breast cancer during the first trimester, so their pregnancies were ended by therapeutic abortion. Although 1 of the 3 fetuses who were exposed to chemotherapy in utero at the second or third trimester was born prematurely and low birth weight was diagnosed in the other 2 fetuses, fetal malformation was not seen in any of them. There were 7 normal and 9 cesarean deliveries. Twenty-three healthy babies survived from 27 pregnancies, of whom 17 babies were exposed to chemotherapeutic agents. Conclusions: We reported herein 27 patients with malignancies diagnosed during pregnancy; 17 patients received chemotherapy during the gestational period without any fetal or maternal abnormalities. Because of the low incidence of malignancy during pregnancy, our report is noteworthy.